A Retrospective Evaluation of Femicide Cases Between the Years 2012-2022 in Denizli - Kurtuluş Dereli, Ayşe; Yılmaz, Asena Özge; Acar, Kemalettin (The Bulletin of Legal Medicine, 2024)
Objective: Femicide is the most extreme point of violence against women. In this study, it is aimed to evaluate the sociodemographic characteristics of femicide cases in Denizli and to present solutions by discussing in the light of literature information. Methods: In this study, crime scene investigation reports and autopsy reports of femicide cases in Denizli between 2012 and 2022 were retrospectively analyzed. The cases were evaluated in terms of age, marital status, education level, perpetrator of violence, murder method, crime scene, and cause of death parameters. Results: It was determined that there were 41 femicide cases in Denizli between 2012 and 2022. In the majority of cases, the perpetrator was a intimate partner. The homicide took place mostly in the woman’s home, and the most common method of killing was firearms. Conclusion: Policies to prevent violence against women, expanding access to post-violence services, and strengthening laws, policies and action plans to end violence can be effective in reducing femicide.